Comparação de transcriptomas por sequenciamento de próxima geração em tecidos de cabeça de duas espécies de moscas-das-frutas, Anastrepha fratercules e Anastrepha obliqua - Rezende, Victor Borges (Universidade Federal de São Carlos, 2014)
We studied patterns of gene expression in two closely related species of fruit flies of the genus Anastrepha (Diptera: Tephritidea), A. fraterculus and A. obliqua, with the goal of finding candidate genes related to the recent differentiation process between these species. In order to do this, we used the Next-generation sequencing (NGS) with RNA-Seq methodology in head tissues of the two species of flies at different stages of the reproductive life for both sexes. After processing and removal of low quality reads we retained over 140 million paired-end reads. These sequences were assembled into individual transcriptomes for each species and a pooled transcriptome, with 154,787 contigs, representing both species. Based on the results of the assemblies, annotation and mapping we prepared two separate manuscripts, one describing the libraries for each species and a combined analysis and a second that investigate the contigs involved with species differences and their patterns of expression. These data reveal 1991 genes with differential expression in at least one comparison among different reproductive stages. It is noteworthy that we observed twice as many genes with differential expression when contrasting males than with females. Several of these genes were associated to odour, such as Odorant Binding proteins and visgum, suggesting that behavioral changes in food sources, mating choice, or breeding and oviposition sites might be involved with species differences.We also identified two large sets of genes that are differentially expressed between the species, one being underexpressed in A. obliqua and overexpressed in A. fraterculus and the other that had a reverse pattern. We used a differentiation index of SNPs per contig () and pairwise tests of positive selection between the sequences, and analysis of the substitution amino acid type caused by SNPs to identify 7 genes there are candidates to be related to the speciation process between A. fraterculus and A. obliqua.
Keywords: Genética e evolução; Anastrepha fraterculus; Anastrepha obliqua; Expressão gênica; Transcriptoma; Transcriptome; Next-generation sequencing; Differential gene expression; SNP calling; CIENCIAS BIOLOGICAS::GENETICA